Gaston d'Orléans et sa cour : étude litteraire - Abraham, Claude Kurt, 1931- (Book collections on Project MUSE., 1964)
"The annotated text, followed by a listing of principal sources and a selective bibliography, has the dual purpose of tracing a biography of G. D'Orleans and depicting his patronage of the arts."--